Sarcopenia is not associated with hypertension, but sarcopenic obesity increases risk of hypertension: a 7-year cohort study - Runfen Du; Junchao Yuan; Yunda Huang; Guihua Jiang; Zhiping Duan; Hong Yang; Wei Huang (Frontiers in Public Health)
BackgroundSarcopenia, sarcopenic obesity, and hypertension are all widespread public health problems in middle-aged and older populations, and their association is controversial. The purpose of this study is to analyze the relationship between obesity, sarcopenia, and sarcopenic obesity with hypertension in a middle-aged and older community population in China through a large-scale longitudinal design.MethodsIn this cohort study with 7 years of follow-up, the study population was drawn from participants in the China Health and Retirement Longitudinal Study (CHARLS) in 2011 and followed up in 2013, 2015, and 2018. The diagnostic criteria for sarcopenia were based on the consensus recommendations issued by the Asian Working Group for Sarcopenia (AWGS) in 2019. The diagnosis of obesity is based on body mass index and waist circumference. Sarcopenic obesity is defined as the coexistence of sarcopenia and obesity. Cox proportional risk regression models were used to analyze the association of obesity, sarcopenia, and sarcopenic obesity with hypertension.ResultsA total of 7,301 participants with a mean age of 58 ± 8.8 were enrolled in the study, and 51.9% females. A total of 1,957 participants had a new onset of hypertension after 7 years of follow-up. In a multifactorial analysis, obesity and sarcopenic obesity were associated with hypertension; hazard ratios (HRs) and 95% confidence intervals (CIs) were 1.67 (1.43 ~ 1.96), p < 0.001, and 1.61 (1.09 ~ 2.37), p = 0.017. Sarcopenia and hypertension were not significantly associated; the HR and 95% CI were 1.17 (0.9 ~ 1.52), p = 0.23.ConclusionThere is no significant correlation between sarcopenia and hypertension, but obesity and sarcopenic obesity increase the risk of hypertension. Targeted management of middle-aged and older people with sarcopenic obesity is needed in public health efforts.